TINJAUAN YURIDIS TERHADAP TINDAKAN ABORSI TANPA IZIN (STUDI KASUS PUTUSAN NOMOR 407/PID.SUS/2020/PN JKT.PST) - Hafidz Muhammad,; PL Tobing, (The Juris, 2022)
The issue of abortion is no longer a public secret and is not a taboo subject to discuss. This is because abortions that occur today have become an actual thing and their events can occur anywhere and can be carried out by various groups, whether they are carried out by teenagers who are involved in promiscuity or adults who do not want to be burdened with responsibility and did not want the birth of the baby into this world. The problem in this paper is: What is the legal basis for regulating the crime of abortion in a positive legal perspective? and What are the basic considerations of the Panel of Judges in deciding case Number 407 /Pid.Sus/2020/PN Jkt.Pst. The research method used is a normative research method that focuses on library research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the applicable provisions or laws and regulations. The results of the study show that arrangements related to abortion are regulated in two laws, namely the Criminal Code (KUHP) Articles 299, 346, 347, 348 and 349 and regulated in Law no. 36 of 2009 concerning Health Articles 75, 76.77.